The Efficacy of Acupuncture on Patients with Erectile Dysfunction: A Review. (9th May 2022) - Wang, Hao; Zhao, Ming; Zhang, Jiwei; Yan, Bin; Liu, Shengjing; Zhao, Feng; Guo, Jun; Wang, Fu
Abstract : Erectile dysfunction (ED) is one of the most common sexual dysfunctions in men. The prevalence of ED has been increasing in recent years, which has critically affected male reproductive health and quality of life. According to various guidelines, phosphodiesterase-5 inhibitors are the most commonly recommended drugs for treating ED. However, many patients turn to alternative therapies because of adverse reactions, such as headache, and the poor efficacy of these drugs. Acupuncture is a long-established treatment in traditional Chinese medicine (TCM) and has been approved by the World Health Organization for improving penile erection as well as other discomforts in patients. However, previous systematic reviews have not discussed the characteristics and the related mechanisms of acupuncture treatment. Therefore, this study focuses on summarizing the characteristics and advantages of TCM in acupuncture treatment for ED based on relevant literature and on predicting and analyzing the related mechanisms.